Relationship between pulse pressure variation and stroke volume variation with changes in cardiac index during hypotension in patients undergoing major spine surgeries in prone position - A prospective observational study - Rajasekar Arumugam; Susan Thomas; Nisha Sara M Jacob; Ambily Nadaraj; Sajan P George; Georgene Singh (Journal of Anaesthesiology Clinical Pharmacology, 2022)
Background and Aims: Dynamic indices such as pulse pressure variation (PPV) and stroke volume variation (SVV) are better predictors of fluid responsiveness than static indices. There is a strong correlation between PPV and SVV in the prone position when assessed with the fluid challenge. However, this correlation has not been established during intraoperative hypotension. Our study aimed to assess the correlation between PPV and SVV during hypotension in the prone position and its relationship with cardiac index (CI). Material and Methods: Thirty patients aged 18–70 years of ASA class I–III, undergoing spine procedures in the prone position were recruited for this prospective observational study. Hemodynamic variables such as heart rate (HR), mean arterial pressure (MAP), PPV, SVV, and CI were measured at baseline (after induction of anesthesia and positioning in the prone position). This set of variables were collected at the time of hypotension (T-before) and after correction (T-after) with either fluids or vasopressors. HR and MAP are presented as median with inter quartile range and compared by Mann-Whitney U test. Reliability was measured by intraclass correlation coefficients (ICC). Generalized estimating equations were performed to assess the change of CI with changes in PPV and SVV. Results: A statistically significant linear relationship between PPV and SVV was observed. The ICC between change in PPV and SVV during hypotension was 0.9143, and after the intervention was 0.9091 (P < 0.001). Regression of changes in PPV and SVV on changes in CI depicted the reciprocal change in CI which was not statistically significant. Conclusion: PPV is a reliable surrogate of SVV during intraoperative hypotension in the prone position.